Two Doses of SARS-CoV-2 Vaccines Reduce Risk of Death Due to COVID-19 in Solid Organ Transplant Recipients: Preliminary Outcomes From a UK Registry Linkage Analysis. Issue 11 (23rd July 2021) - Ravanan, Rommel; Mumford, Lisa; Ushiro-Lumb, Ines; Callaghan, Chris; Pettigrew, Gavin; Thorburn, Douglas; Gardiner, Dale; Forsythe, John
Abstract : : Abstract :